Mold design & surface analysis of casted material - Annafi, Mohd Khobori (2010)
Casting is a manufacturing process where a solid is melted, heated to proper temperature, and is then poured into a cavity or mold, which contains it in the proper shape during solidification. Casting process generally is classified as expendable mold or permanent mold. These researches consist of design and fabricate mould for die casting process and analyze the structure and surfaces of the casted materials. Objective of the research is to design and fabricates mold for tensile test specimen, following ASTM E8 standard and to analysis the surface and structure of casted material. Material that has been used for mold is mild steel meanwhile casted material is aluminum alloys. Furthermore, this research is consisting of several main processes which mold is design by Solidwork software and simulation for machining process is done by mastercam software. Meanwhile, fabrication process is done by CNC milling machine and finally perform casting process to produce casted materials. Subsequently, these researches were carried out in order to analyze the effect of surface roughness, dimension and thickness values on casted material by 3 different pre-heated temperatures. For these experiments, 3 measurements were measured at 3 casted materials from three different pre-heated mold temperatures. Therefore, 100 °c, 250 °c and 350 °c temperatures were tested to observe the effects of surface roughness, dimension and thickness of casted material. For surface roughness,the analysis of results indicated the value of surface roughness does not affected by different preheated temperature. Other than that, the values of thickness and dimensions of the casted material were slightly decreased at different pre-heated temperature. When the dimension and thickness pre-heated at 150°c, the values decreased compared with other pre-heated temperature. For pre-heated mold temperature 150°c, the dimension and thickness values are 8.18mm and 3.29 mm. Meanwhile, for 250°c and 350°c pre-heated mold temperature, the dimension and thickness values is 12.55 mm, 12.57 mm, 3.37 mm and 3.54 mm. For pre- heated temperature 200°c and 350°c, the values of dimension and thickness not significantly different. In addition, the morphology examinations through scanning electron microscope (SEM) were examined in order to investigate the effects of porosity defects by different pre-heated mold temperature. The result shows that porosity still occurred at casted material with different pre-heated mold temperatures. However, for pre- heated 150°c mold temperature, porosity occurred more than other pre-heated mold temperature. It proved that the undesirable pre-heated mold temperatures causes more porosity will occurred on casted material. The appropriate pre-heated temperature is 280 °c and 350 °c for aluminum alloys to produce good casted products.